(untitled) (The Science Post, 2025)
Prescription optimization in outpatient care has largely been driven by cost-containment measures such as generic substitution and the adoption of digital prescribing tools. However, the success of these strategies ultimately depends on patient trust, perceptions of safety, and willingness to adhere to substituted therapies. This paper explores patient- centered approaches to optimizing outpatient prescriptions, emphasizing the need to balance cost savings with equitable access, safety, and transparency. Drawing from recent studies, it highlights how patient education, shared decision-making, and transparent communication significantly influence the acceptance of substitution strategies. Furthermore, the literature reveals that combining clinical decision-support systems (CDSS) with patient engagement interventions leads to improved adherence and higher satisfaction. By integrating patient perspectives into substitution frameworks, healthcare systems can achieve sustainable prescription practices that are both clinically effective and socially acceptable.